VERBAL AND NON-VERBAL SIGNS PORTRAYING FEMINISM AND ITS EXPLOITAITON IN “WALL’S MAGNUM PINK AND BLACK ICE-CREAM ADVERTISEMENT” - I Wayan Sidha Karya; Ni Kadek Widiastuti; Kartika Dewi Maharta (SPHOTA: Jurnal Linguistik dan Sastra, 2018)
ABSTRACT In this study, the researcher tried to decipher the message conveyed in the Wall’s Magnum Pink and Black Ice-cream advertisement, portraying feminism for the advocacy of women's rights on the basis of the equality of the sexes. And yet, contradictively it was also at the same time liable to exploitation. Using the catch words such as Magnum and the letter M as well as woman pictures and changing of colors and movements and woman expressions, it was obvious that the advertiser was in the position of trying to catch the audience’s attention. Two things that immediately came into the audience’s attentions when watching the advertisement were the woman with her expressions and colors and, all things that had to do with the ice-cream. The data collected from the series of the movies the spoken words were then analyzed using the descriptive qualitative method, in which they were described and interpreted along the lines of semiotic theories as proposed by well-known semioticians, such as Ferdinand de Saussure, Roland Barthes and Pierce and Daniel chandler, who talked about the relation between/among sign vehicle/signifier/symbol, concept/signified/referent, and sense/thought. In the semiotics there is a cover term to include the three of them; this is SIGN. The colors of the ice-cream, pink and black are symbols of cheerfulness and elegance respectively. Whereas the woman who appeared in pink and black in the advertisement, besides being symbols for cheerfulness and elegance, was also a show off for feminism. She had the freedom in her actions and speech or expression. Key words: sign, signifier, signified, symbol, feminism